Penerapan Geostatistik Dalam Analisis Spasi Lubang Bor Bagi Perencana Eksplorasi Tambang - Irfan Marwanza; Mohamad Nur Hariawan; Danu Putra (Abdimas Universal, 2022)
Currently, in planning for mineral and coal exploration drilling, there are still many questions about how to determine the optimal borehole distance for resource classification, because the determination of the number of drill holes will be highly correlated with the expenditure of exploration funds. The solution to answer these questions is to increase the knowledge and understanding of exploration planners regarding borehole distance analysis for resource classification, especially by using geostatistical methods. In this case, the technique used is global estimation variance. The implementation of community service in the form of workshops is carried out in various stages, including the planning stage, workshops and activity evaluation. The results of this activity can increase the understanding and knowledge of the participants about the concept of geostatistics and determining the optimal number of drill holes. The conclusion of the workshop that was carried out was that almost all participants were able to receive the material presented, it was seen from the very intensive discussion at the end of the event and at the end of the event the participants wanted further training by increasing practice.